Evolution of epitaxial BaTiO3 on SrTiO3-buffered Si: Phase field analysis - Li, Wente; Landis, Chad M.; Demkov, Alexander A. (Journal of applied physics, 2022)
Barium titanate (BaTiO3) is a promising candidate for electro-optical modulators in Si photonics. The BaTiO3 ferroelectric domain morphology is strongly affected by thermal, electrical, and mechanical conditions and, in turn, profoundly influences the film's optical properties. Because BaTiO3 film growth takes place at a relatively high temperature, upon cooling, the film is subject to complex thermal effects that involve changes in the crystal phase, the emergence of ferroelectricity, and variations in the strain level. We use a phase field model to describe the evolution of the BaTiO3 thin film domain morphology upon cooling from growth to room temperature. We demonstrate that cooling under different cooling scenarios results in different domain morphologies. Our simulations provide a clear temperature–strain map and thermal strategy for controllable BaTiO3 epitaxy on the SrTiO3-buffered Si substrate.